Central mesencephalic reticular formation control of the near response: lens accommodation circuits - May, Paul J. (J Neurophysiol, 2019)
To view a nearby target, the three components of the near response are brought into play: 1) the eyes are converged through contraction of the medial rectus muscles to direct both foveae at the target, 2) the ciliary muscle contracts to allow the lens to thicken, increasing its refractive power to focus the near target on the retina, and 3) the pupil constricts to increase depth of field. In this study, we utilized retrograde transsynaptic transport of the N2c strain of rabies virus injected into the ciliary body of one eye of macaque monkeys to identify premotor neurons that control lens accommodation. We previously used this approach to label a premotor population located in the supraoculomotor area. In the present report, we describe a set of neurons located bilaterally in the central mesencephalic reticular formation that are labeled in the same time frame as the supraoculomotor area population, indicating their premotor character. The labeled premotor neurons are mostly multipolar cells, with long, very sparsely branched dendrites. They form a band that stretches across the core of the midbrain reticular formation. This population appears to be continuous with the premotor near-response neurons located in the supraoculomotor area at the level of the caudal central subdivision of the oculomotor nucleus. The central mesencephalic reticular formation has previously been associated with horizontal saccadic eye movements, so these premotor cells might be involved in controlling lens accommodation during disjunctive saccades. Alternatively, they may represent a population that controls vergence velocity. NEW & NOTEWORTHY This report uses transsynaptic transport of rabies virus to provide new evidence that the central mesencephalic reticular formation (cMRF) contains premotor neurons controlling lens accommodation. When combined with other recent reports that the cMRF also contains premotor neurons supplying medial rectus motoneurons, these results indicate that this portion of the reticular formation plays an important role in directing the near response and disjunctive saccades when viewers look between targets located at different distances.